PROGRAM PELATIHAN KARYAWAN PADA DIVISI HUMAN RESOURCE DEVELOPMENT( STUDI KASUS: PT NEYDA RIZKI) - Kamal, Fahmi (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2014)
The training program at a company is required to improve the quality of work that affect the achievement of objectives of a company. The purpose of this study was to determine the types of research conducted by PT Neyda RIZKI in implementing employee training programs at every new and old employees to get to know their work areas. The research method that I use is the method of observation / interview, and literature. Based on observations and interviews at the Human Resource Development Division of PT Neyda RIZKI training starts from the planning stages to the training evaluation training. This type of training is used for new employee orientation, training methods on the job training and of the job training for new employees and old employees that provide benefits for companies and employees to achieve results or targets satisfactory work. The training provided is Leadership, Decision Making, Safety Awareness, Excellent Service, Taxation, Computer Organization Development and Filing. Until recently conducted a training program on Human Resource Development division goes well and smoothly. Training is the best way to provide the skills and mastery of work in the field of their work. Good training can have a positive impact in identifying and improving the quality of work of each employee.  Keywords: Employee Training